The Role of Pharmacological and Nursing Support in Enhancing Physical Therapy Outcomes for Neurological Disorders: Review - Albaqami, Saad Mohammed Sunaytan; Almutairi, Saeed Fahaed; Almutairi, Faisal Muhayya Bin Ayidh; Moubark, Mesfer Abdullh; Al Salem , Safa Saleh; Alwan, Ibtesam Ali; Sufiany, Amani Yahia; Mubaraki, Abeer Yahya Ahmed; Alanazi, Ghadeer Humaidhi; Alharthy, Tahani Abdullah Hammad; Alkuwaykibi, Bader Mushahhin Rafifah; Al Bishi, Ashwag Saad Hnif (Journal of Ecohumanism, 2024)
Neurological disorders frequently lead to significant sleep disturbances, which can hinder rehabilitation outcomes and negatively impact patients' quality of life. Sleep issues are prevalent among individuals with conditions such as Parkinson's disease, multiple sclerosis, and after traumatic brain injuries. Addressing these disturbances is crucial for enhancing the effectiveness of physical therapy.This systematic review evaluates the effects of pharmacological and non-pharmacological interventions, particularly physical therapy, on sleep disturbances in patients with neurological disorders. An extensive literature search was conducted across databases, including MEDLINE and the Physiotherapy Evidence Database (PEDro), using specific keywords related to sleep disturbances and rehabilitation. Various assessment tools, including the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI), were utilized to evaluate sleep quality and disturbances.The review identified ten studies, with six included in a meta-analysis. Findings suggest that physical therapy interventions significantly improve sleep quality and reduce disturbances among individuals with neurological conditions. Multimodal physical therapy approaches, which combine aerobic and resistance training, showed particularly favorable outcomes, enhancing sleep efficiency and reducing reliance on sleep medications. Physical therapy emerges as an effective non-pharmacological strategy to mitigate sleep disturbances in patients with neurological disorders. Incorporating tailored physical therapy protocols into rehabilitation programs could enhance treatment outcomes and improve overall quality of life for these patients.